Bhabinkamtibmas dalam Menjaga Keamanan dari Paham Radikalisme di Wilayah Hukum Polsek Denpasar Timur - Ni Nyoman Septiana Dewi; A.A SAGUNG LAKSMI DEWI; I MADE MINGGU WIDYANTARA (Warmadewa Press, 2020)
Bali is one of the tourist destinations; many come for a vacation and enjoy the beauty of the island of Bali, both foreign nationals and local tourists. The number of local tourists and foreign nationals who come to Bali is used by a handful of people to commit crimes, as recently happened in the jurisdiction of the East Denpasar Police. The joint team of Densus 88 Police Headquarters, Task Force CTOC and Brimob Polda Bali, on Tuesday, June 26 2018 at 20.30 WITA, raided one of the houses on Jl. Gandapura related to Radicalism Group. This study explores two issues, namely Bhabinkamtibmas efforts in maintaining security from radicalism and the factors that can influence the development of radicalism. The method of research used in this study is normative legal research using a statutory approach. Bhabinkamtibmas are police officers who work at the village to sub-district level and carry out a preventive function by partnering with community members, and have an important role in preventing the development of radicalism. The conclusion from the results of this study is that radicalism appears as a notion or ideology that demands change and renewal of social and political systems by means of (Sztompka, 1993; Odea, 1996). As an effort by Babhinkamtibmas to prevent the development of factors that can cause radicalism, legal guidance and counseling and social security are provided to increase legal awareness and social security by upholding human rights (HAM) in the jurisdiction of the East Denpasar Police.